A SWOT Analysis for Enhancing Port Operations at Sukamara - Munthe, Intan Ayu P.; Syamsudin, Achmad; Giovanni, Jonathan (JSM: Jurnal Sains Manajemen, 2024)
The objective of this study is to uncover (1) the identification of SWOT factors in the operations of Sukamara Port and (2) the solutions for enhancing the operations of Sukamara Port. The survey included a total of 40 respondents, consisting of staff members at KSOP Sukamara and those employed at Sukamara Port. The data analysis procedure incorporates qualitative descriptive analysis, IFAS analysis (Internal Factors Analysis Summary), EFAS analysis (External Factors Analysis Summary), and SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). The study findings suggest that Sukamara Port is located in the negative quadrant of the defensive category. The quadrant refers to a scenario in which the company's state is not meeting expectations or, in other words, is unfavorabl